APPLICATION OF PINEAPPLE WASTE FOR BIOETHANOL PRODUCTION AS A CLEAN ENERGY SOURCE FOR PETROL-POWERED ENGINE - Lawan, Salisu M.; Abba, I.; Bala, D.; Abdullahi, A. Y.; Aminu, A. (FUDMA JOURNAL OF SCIENCES, 2023)
Bioethanol derived from agricultural waste offers a sustainable alternative to conventional energy source such as fossil fuels as the demand for energy continues to increase and the supply depletes. In Malaysia, agricultural wastes are potential to be one of the feedstock for producing bioethanol due to low cost and readily available. The utilization of agricultural waste for bioethanol production also does not disturb the consumer food supply as it is based on waste-to-energy concept. Bioethanol produced is then blended with gasoline (petrol) to create a mixture that can be used in modern vehicles. In this study, pineapple waste has been chosen to investigate the feasibility of using pineapple waste as a substrate to produce bioethanol. Different parts of pineapple waste were treated with different acid concentrations (5, 10 and 15 %, v/v) at a constant high temperature and pressure which were later fermented for a time period of 48 hours. At the same time, one small-scale bioreactor was also fabricated to perform the fermentation of pineapple waste. It was found that the pineapple residue contained a good amount of glucose up to 455.84 g/L when 15% (v/v) H2SO4 used for acid hydrolysis was carried out. However, the fermentation of pineapple pulp had produced the highest bioethanol concentration (375.43 g/L) when 15% (v/v) H2SO4used for acid hydrolysis was performed. Bioethanol concentration obtained through the fabrication of small-scale reactor on the other hand was 374.78 g/L
Keywords: Pineapple waste, Acid hydrolysis, Bioethanol production, Glucose consumption